Reactivity of redox cycled Fe-bearing subsurface sediments towards hexavalent chromium reduction. (1st May 2019) - Bishop, Michael E.; Dong, Hailiang; Glasser, Paul; Briggs, Brandon R.; Pentrak, Martin; Stucki, Joseph W.; Boyanov, Maxim I.; Kemner, Kenneth M.; Kovarik, Libor
Abstract: Structural Fe(II) in clay minerals and natural sediments is known to reduce Cr(VI) to Cr(III), but the effect of redox-cycled Fe-bearing natural sediments on Cr(VI) reduction kinetics is poorly understood. The objective of this study was to understand the kinetics and mechanisms of Cr(VI) reduction by Fe(II) in redox cycled natural sediment. Fe-bearing sediment was collected from the Ringold formation in the 300 area of Hanford, Washington, United States. Fe redox cycling of the sediment was accomplished via four cycles of bioreduction of structural Fe(III) in Hanford sediment and air oxidation of the resulting Fe(II). Bio-produced Fe(II) in Hanford sediment from each redox cycle was utilized to reduce Cr(VI) at three temperatures (10, 20 and 30 °C). The initial rate of Cr(VI) reduction generally increased with each redox cycle, which was more pronounced at high temperatures. The amount of Fe(II) oxidized to the amount of Cr(VI) reduced was close to the expected stoichiometric ratio of 3. Aqueous concentrations of Si, Al, and Fe revealed some dissolution of the sediment after reaction with Cr(VI). X-ray diffraction (XRD) and scanning electron microscopy (SEM) detected secondary mineral formation. Mössbauer data showed that the oxidation of Fe(II) was coupled with the reduction of Cr(VI) but no Fe-oxides/oxyhydroxides formed. Transmission electron microscopy (TEM), electron energy loss spectroscopy (EELS), XANES, and EXAFS were performed for representative reduced Cr solids that formed from reduction of Cr(VI) by sediment-associated Fe(II) at 30 °C. TEM revealed that the d-spacing of Cr-reacted montmorillonite at 30 °C, a dominant Fe-bearing mineral in Hanford sediment, expanded from 10 Å to 13 Å. This layer expansion was likely due to intercalation of reduced Cr(III) into the interlayer space of the montmorillonite structure. EELS exhibited an L2 absorption peak at 586.0 eV and an L3 absorption peak at 577.0 eV, suggestive of Cr(III) in a hydroxide mineral phase. Similarly, XANES and EXAFS analyses confirmed Cr(VI) reduction to Cr(OH)3 at 30 °C and indicated an edge-sharing coordination of the Cr(III) octahedra to 2–3 other Cr or metal ions. This study has important implications for understanding the reactivity of clay-rich sediment towards Cr(VI) reduction at contaminated sites and the stability of the reduced Cr(III).